R-spondins can potentiate WNT signaling without LGRs - Lebensohn, Andres M (eLife, 2018)
The WNT signaling pathway regulates patterning and morphogenesis during development and promotes tissue renewal and regeneration in adults. The R-spondin (RSPO) family of four secreted proteins, RSPO1-4, amplifies target cell sensitivity to WNT ligands by increasing WNT receptor levels. Leucine-rich repeat-containing G-protein coupled receptors (LGRs) 4-6 are considered obligate high-affinity receptors for RSPOs. We discovered that RSPO2 and RSPO3, but not RSPO1 or RSPO4, can potentiate WNT/β-catenin signaling in the absence of all three LGRs. By mapping the domains on RSPO3 that are necessary and sufficient for this activity, we show that the requirement for LGRs is dictated by the interaction between RSPOs and the ZNRF3/RNF43 E3 ubiquitin ligases and that LGR-independent signaling depends on heparan sulfate proteoglycans (HSPGs). We propose that RSPOs can potentiate WNT signals through distinct mechanisms that differ in their use of either LGRs or HSPGs, with implications for understanding their biological functions.